Predictors of fetal anemia and cord blood malaria parasitemia among newborns of HIV-positive mothers - Laar, A.K.; Grant, F.; Addo, Y.; Soyiri, I.; Nkansah, B.; Abugri, J.; Laar, A.S.; Ampofo, W.K.; Tuakli, J.M.; Quaki, I.A. (Springer, 2013)
Malaria and HIV infections during pregnancy can individually or jointly unleash or confound pregnancy outcomes. Two of the probable outcomes are fetal anemia and cord blood malaria parasitemia. We determined clinical and demographic factors associated with fetal anemia and cord blood malaria parasitemia in newborns of HIV-positive women from two districts in Ghana. We enrolled 1,154 antenatal attendees (443 HIV-positive and 711 HIV-negative) of which 66% were prospectively followed up at delivery. Maternal malaria parasitemia, and anemia rates among HIV+ participants at enrolment were 20.3% and 78.7% respectively, and 12.8% and 51.6% among HIV- participants. Multivariate linear and logistic regression models were used to study associations. Prevalence of fetal anemia (cord hemoglobin level < 12.5 g/dL) and cord parasitemia (presence of P. falciparum in cord blood at delivery) were 57.3% and 24.4% respectively. Factors found to be associated with fetal anemia were maternal malaria parasitemia and maternal anemia. Infant cord hemoglobin status at delivery was positively and significantly associated with maternal hemoglobin and gestational age whilst female gender of infant was negatively associated with cord hemoglobin status. Maternal malaria parasitemia status at recruitment and female gender of infant were positively associated with infant cord malaria parasitemia status. Our data show that newborns of women infected with HIV and/or malaria are at increased risk of anemia and also cord blood malaria parasitemia. Prevention of malaria infection during pregnancy may reduce the incidence of both adverse perinatal outcomes.